Pemanfaatan Limbah Plastik Dan Serbuk Gergaji Kayu Sebagai Bahan Pengisi Bambu Komposit Setempat - I Wayan Sugiartha; Aryani Rofaida; Rini Srikus Saptaningtyas; Teti Handayani (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2021)
This study aims to determine the mechanical properties (compressive strength and shear strength) of bamboo filled with PET plastic and wood sawdust. Five variations of test objects were made, namely BK-0 (bamboo without filler as a control), BK-1 (bamboo filled with PET plastic), BK-2 (bamboo filled with PET plastic + adhesive coated), BK-3 (bamboo filled with PET plastic + powder wood saw), BK-4 (bamboo filled with PET plastic + wood sawdust and coated with adhesive). The test results give the value of the compressive strength of bamboo from BK-0 to BK-4 in a row of 22.7 MPa, 29.4 MPa, 32.7 MPa, 33.2 MPa, 35.7 MPa or an increase in the compressive strength of BK-0 in a row by 30%, 44%, 46%, and 57%. Meanwhile, the shear strength of bamboo from BK-0 to BK-4 is 4.55 MPa, 5.00 MPa, 5.05 MPa, 5.40 MPa, 5.50 MPa or an increase in shear strength to BK-0 is 10%, 11%, respectively. , 19%, and 21%.